THE EFFECTS OF COMMONLY USED DRUGS ON ORTHODONTIC TOOTH MOVEMENT : A SYSTEMATIC REVIEW - BATMARAJ; PROF.UMASHANKAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The objective of this review of literature is to evaluate the effect of different types of drugs being used in orthodontic. This review will brief out the different views by various authors regarding the group of drug that effect orthodontic tooth movement. Method: The electronic database of PubMed, Wiley online library, and Science Direct were used. The search strategies are presented in Appendix 1. The period of electronic search was from January 1970 to November 2012. A single author conducted the electronic search independently based on the inclusion criteria. Â Results: The search revealed a total of 189 articles and abstracts found through Pub med, Wiley online library and science direct. After reading the title and abstract 75 was excluded from the review of literature. Application of inclusion criteria resulted in 48 articles used for data extraction and subsequent review Â Conclusion: As more and more chemical analogues are being used in the form of new drugs to avoid resistance, today's clinicians should mandatorily update his knowledge on the clinical efficacy of the new drugs as well as the beneficial and harmful effects on human tissues .Â It is always advisable for a dentist to confirm with the family physician or the concerned physician for fitness of the patients who undergo orthodontics treatment involving tooth movement.